Analisis Hubungan Manajemen Stres dengan Keselamatan Kerja Teknisi Telekomunikasi, Navigasi dan Pengamatan Penerbangan di Bandara Udara Kuala Namu - Mutiara Sitopu; Afandi Sahputra (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
In the field of aviation are required to work professionally, especially technicians. So that it burdens the technicians to always be in a healthy condition both physically and mentally. If the technicians experience stress in doing their work, it will have a bad impact on the aviation sector. Therefore, in order to prevent bad things from happening, an analysis of the relationship between stress management and work safety is carried out. technician in charge of telecommunications, navigation and flight observation at Kuala Namu Airport. Some of the factors that are observed in this study are intrinsic factors in work (workload, routine and noise), career development (job promotion, salary satisfaction and education and training), and worker factors (age, education, years of service). which shows a relationship with work stress management for telecommunications, navigation and flight safety technicians at Kuala Namu Deli Serdang Airport in 2021 is workload, routine, noise. Keywords: stress management, aviation